Cognitive Fitness: Harnessing the Strength of Exerkines for Aging and Metabolic Challenges - Mona Saheli; Mandana Moshrefi; Masoumeh Baghalishahi; Amirhossein Mohkami; Yaser Firouzi; Katsuhiko Suzuki; Kayvan Khoramipour (MDPI AG, 2024)
Addressing cognitive impairment (CI) represents a significant global challenge in health and social care. Evidence suggests that aging and metabolic disorders increase the risk of CI, yet promisingly, physical exercise has been identified as a potential ameliorative factor. Specifically, there is a growing understanding that exercise-induced cognitive improvement may be mediated by molecules known as exerkines. This review delves into the potential impact of aging and metabolic disorders on CI, elucidating the mechanisms through which various exerkines may bolster cognitive function in this context. Additionally, the discussion extends to the role of exerkines in facilitating stem cell mobilization, offering a potential avenue for improving cognitive impairment.